Analysis of the Implementation of Murabahah Contract in Fertilizer Payments with a Post-Harvest Payment Scheme from the Perspective of Islamic Financial Institutions - A. Kasmianti; Abdulahanaa; Shadriyah (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2025)
This study aims to analyze the implementation of the murabahah contract in post-harvest fertilizer payments in Tadang Palie Village, Ulaweng District, Bone Regency, and to assess it from the perspective of Islamic financial institutions. Murabahah is a sale contract in Islamic banking where the purchase price and profit margin are agreed upon at the start of the transaction. The study uses a qualitative descriptive method, with data collected through observation, interviews, and documentation involving corn farmers. The findings show that post-harvest fertilizer payments are commonly practiced among farmers, providing convenience by allowing them to obtain fertilizer without upfront payment. However, this system carries risks, particularly the possibility of payment default due to uncertain harvest outcomes. From the Islamic financial perspective, the application of the murabahah contract in this scheme is generally in accordance with sharia principles, as it fulfills the pillars and conditions of a valid contract. Still, there are important aspects that require attention, such as price transparency and effective risk management. This research is expected to provide useful insights for academics, farmers, and Islamic financial institutions in understanding the practical implementation of the murabahah contract, particularly in agricultural financing with a post-harvest payment system.